2009
DOI: 10.1007/s10878-009-9232-y
|View full text |Cite
|
Sign up to set email alerts
|

Approximating the chromatic index of multigraphs

Abstract: It is well known that if G is a multigraph then χ (G) ≥ χ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…This technical fact was used in several results using Tashkinov trees, for example [1,5,11]. Our main lemma, Lemma 8, is also based on this parameter.…”
Section: Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technical fact was used in several results using Tashkinov trees, for example [1,5,11]. Our main lemma, Lemma 8, is also based on this parameter.…”
Section: Toolsmentioning
confidence: 99%
“…Here we mention just the results that directly relate to this note. The best known approximate version is as follows, due to Scheide [11] (independently proved by Chen, Yu and Zang [1], see also [12] and [2]), who proved that the conjecture is true when ⌈ρ(G)⌉ ≥ ∆ +  ∆−1 2 .…”
Section: Conjecture 2 For Every Multigraphmentioning
confidence: 99%
“…We remark that many of the results and ideas used here have appeared in other works (e.g. [6,26,30,31]) but in order to keep this paper self-contained we include all proofs. Lemma 2.8.…”
Section: Toolsmentioning
confidence: 99%
“…In the past few years, there were several improvements for the upper bound on χ ′ (G) in terms of ρ(G), see, e.g., [6,14,15,16,24,26,27,31]. In [6], and independently [26], it was shown that χ ′ (G) ≤ max{∆+ ∆ 2 , ⌈ρ(G)⌉}. A very recent breakthrough by Chen, Gao, Kim, Postle, and Shan [5] proves the best known upper bound of χ ′ (G) ≤ max{∆ + 3 ∆ 2 , ⌈ρ(G)⌉}.…”
Section: Introductionmentioning
confidence: 99%
“…Feige et al [12] show a polynomial-time algorithm which, for a given multigraph and an integer k, finds a subgraph H such that |E(H)| ≥ OPT, ∆(H) ≤ k + 1 and Γ(H) ≤ k+ √ k + 1+2, where OPT is the number of edges in the maximum k-edge colorable sugraph of G, and Γ(H) is the odd density of H, defined as Γ(H) = max S⊆V (H),|S|≥2 |E(S)| ⌊|S|/2⌋ . The subgraph H can be edge-colored with at most max{∆+ ∆/2, ⌈Γ(H)⌉} ≤ ⌈k + √ k + 1+2⌉ colors in n O( √ k) -time by an algorithm of Chen, Yu and Zang [3]. By choosing the k largest color classes as a solution this gives a k/⌈k + √ k + 1 + 2⌉-approximation.…”
Section: Approximation Algorithms For the Max K-ecs Problemmentioning
confidence: 99%